Diversidade genética do Zika virus no Estado do Espírito Santo - Rodrigues, Fernanda Mariano Garcia de Souza (2018)
Zika virus (ZIKV) is an arbovirus belonging to the genus Flavivirus of the Flaviviridae family. Two main lineages are recognized, Asian and African, the Asian lineage was found in Brazil. The symptoms are usually mild, but there are reports of cases of death and neurological manifestations. Viral genetic variations are related to the differences in the clinical manifestations of the disease, and research on the genome, phylogeny and geographical distribution of the virus can clarify how these variations affect the clinical manifestation of ZIKV and the development of biotechnological products. Despite the importance, few studies evaluate viral genetic variations. This study carried out a population-based epidemiological and phylogenetic approach that analyzed the genetic diversity of ZIKV in Espírito Santo (ES), and the phylogenetic relationships of the ZIKV strains identified with GenBank available viral sequences. It was found that the municipalities of Vitória, Cariacica and Cachoeiro de Itapemirim are the most affected, and the current lineage in ES is the Asian, as well as in the rest of the country. Four variants were found in 2 genes studied, in the E A1023G and C1050T gene and in the NS5 gene C1891T and T1945C. Variations A1023T and C1891T were first described in Asian lines in this work, and the variations C1050T and T1945C were previously described in Asian lineage only once in a sequence from Rio de Janeiro and three sequences in China, respectively. Finally, although the genetic variations found in the ES sequences were not associated with the amino acid change, it can not be ruled out that other changes, either in the links between the enzymes and the RNA, or in the structure of the final proteins, can be caused by these variations. The results presented may be useful for future work, allowing an expansion of the database presenting a clearer view of the epidemiology of ZIKV, which may help to determine the geographical origin of a new outbreak and also monitor the effectiveness of the control.